2019
DOI: 10.5194/acp-19-4075-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and kinetics investigations of oligomer formation from Criegee intermediate reactions with hydroxyalkyl hydroperoxides

Abstract: Abstract. Although secondary organic aerosol (SOA) is a major component of PM2.5 and organic aerosol (OA) particles and therefore profoundly influences air quality, climate forcing, and human health, the mechanism of SOA formation via Criegee chemistry is poorly understood. Herein, we perform high-level theoretical calculations to study the gas-phase reaction mechanism and kinetics of four Criegee intermediate (CI) reactions with four hydroxyalkyl hydroperoxides (HHPs) for the first time. The calculated result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 102 publications
0
25
0
Order By: Relevance
“…Actually, we could not evaluate the effect of acidity on the formation of SOA accurately because the acidity of aerosols might impact a series of reactions, and the mechanisms and rates of these reactions at different pH levels were vague. It was noted that Chen et al (2008) found that in the aqueous-phase ozonolysis of methacrolein and methyl vinyl ketone, the yields of products were almost independent of pH, and Zhang et al (2009) also observed this phenomenon in the ozonolysis of α-pinene and β-pinene in the aqueous phase. Thus the effect of the particle acidity on the results might also be limited here, and the accurate estimates of this issue still need further research.…”
Section: Reasons For Different Performances Of Scis Under Different Rh Levelsmentioning
confidence: 97%
“…Actually, we could not evaluate the effect of acidity on the formation of SOA accurately because the acidity of aerosols might impact a series of reactions, and the mechanisms and rates of these reactions at different pH levels were vague. It was noted that Chen et al (2008) found that in the aqueous-phase ozonolysis of methacrolein and methyl vinyl ketone, the yields of products were almost independent of pH, and Zhang et al (2009) also observed this phenomenon in the ozonolysis of α-pinene and β-pinene in the aqueous phase. Thus the effect of the particle acidity on the results might also be limited here, and the accurate estimates of this issue still need further research.…”
Section: Reasons For Different Performances Of Scis Under Different Rh Levelsmentioning
confidence: 97%
“…Furthermore, hydroxymethyl hydroperoxide (HMHP), hydroperoxymethyl formate (HPMF), and α-alkoxyalkyl hydroperoxiedes (AAAHs) are formed during sCI bimolecular reactions, exhibiting large molecular weights and low volatility; these molecules are thought to be closely related to the formation of SOA in the atmosphere. Quantum chemical calculations indicate that CH 2 OO can polymerize with the −OOH and −OH groups of hydroperoxides to form oligomers . Such oligomers may form organic cores in the atmosphere and facilitate the growth of SOA.…”
Section: Oxidantsmentioning
confidence: 99%
“…When the rate constant of limonene-derived SCIs reaction with 2-butanol was assumed as 10 −15 cm 3 molecule −1 s −1 , it was estimated that with the lowest concentration of AA used in experiments, the ratio of the amount of SCIs reacted with 2-butanol to the amount of SCIs reacted with AA was 0.125, which was considered to be not important enough to influence the results. Besides, products formed from SCIs reaction with AA and water might further react with SCIs and impacted aerosols formation (Chen et al, 2019). However, due to the short lifetime and low concentration of SCIs in system, the concentration of SCIs was a limiting factor in bimolecular reactions of SCIs with other products.…”
Section: Analysis On Reaction Mechanismsmentioning
confidence: 99%